Hard Rock Fragmentation in Percussion Drilling Considering Confining Pressure: Insights from an Experimental Study. (December 2021) - Li, Yanliang; Peng, Jianming; Zhang, Pengyu; Huang, Chaoyang
Abstract: Existing numerical simulation studies show that confining pressure has a negative effect on the efficiency of percussion drilling. However, the corresponding systematic experimental studies considering confining pressure have rarely been reported. In this study, single drop weight impact tests were performed on granite samples and the influence of the confining pressure on the crater parameters was analyzed. Besides, the fluorescent approach was adopted to observe the cracks in the damaged samples. The results indicate that confining pressure has a significant adverse effect on rock fragmentation. For instance, the average volume of crater under confining pressure of 20 MPa is 91.5% smaller than that without confining pressure. Meanwhile, the higher the confining pressure, the shorter the cracks. The confining pressure can inhibit the propagation of side cracks around the crater and hinder the expansion of radial cracks to the free surface. Knowing these phenomena and conclusions, we may be able to eliminate or reduce the negative effect of the confining pressure by optimizing the working parameters of the drilling tools and the layout structure of the buttons on the bit. Highlights: The dynamic rock fragmentation performance with confining pressure has been systematically studied by experiments. The influence of the confining pressure on the crater parameters is quantitatively analyzed. Crack evolution under confining pressure was revealed by the fluorescent approach. Confining pressure has a significant adverse effect on dynamic rock fragmentation.